A Simple Thermoplastic Substrate Containing Hierarchical Silica Lamellae for High‐Molecular‐Weight DNA Extraction. Issue 48 (8th November 2016) - Zhang, Ye; Zhang, Yi; Burke, Jeffrey M.; Gleitsman, Kristin; Friedrich, Sarah M.; Liu, Kelvin J.; Wang, Tza‐Huei
Abstract : An inexpensive, magnetic thermoplastic nanomaterial is developed utilizing a hierarchical layering of micro‐ and nanoscale silica lamellae to create a high‐surface‐area and low‐shear substrate capable of capturing vast amounts of ultrahigh‐molecular‐weight DNA. Extraction is performed via a simple 45 min process and is capable of achieving binding capacities up to 1 000 000 times greater than silica microparticles.